EFL Teachersâ Practices on Authentic Writing Assessment at Vocational High School - Rahmat, Abiadi; Rahmadita, Aninda Ristri (UICELL, 2017)
Indonesian Minister of Education and Culture regulations no. 66 of 2013 on National Educational Assessment Standards suggests that authentic assessment practices be employed in performing learning assessment in schools. However, former Minister of MONE reveals that many teachers find this a great challenge to them (Kompas.com, 2014). This study explores VHS EFL teachersâ authentic writing assessment practices in their classrooms. Twenty EFL teachers from nine VHS in East Jakarta have been involved as respondents for the study. A set of questionnaires for teacher respondents, a checklist for analysis of their lesson-plans, and semi-structured interviews for teacher respective students have been employed to collect data for the study. Discussion on findings of the study will be aimed at mapping the observed authentic writing assessment practices of the target respondents. The data obtained from teachersâ questionnaire, studentsâ interview and checklist document analysis, it can be concluded that EFL teachers from nine different vocational schools practice authentic assessment for assessing studentsâ output. The type that teachers chose is intensive. It means teachers concern with studentsâ vocabulary and grammar. Then the technique that they provide for assessing studentsâ writing is essay.